DESIGN A MONITORING SYSTEM OF A SINGLE-PHASE ELECTRICITY METER BASED ON THE INTERNET OF THINGS - Mauludi Manfaluthy; Ade Sunardi; Sinka Wilyanti; Ariep Jaenul; Endang Mulyana (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
This research aims to create systematic monitoring of a single-phase electricity meter that is accompanied by power monitoring features, the amount of electrical energy usage costs and relay control features using internet connections. The design has been carried out using PZEM-004T current and voltage sensors. The microcontrollers have been implemented by using ESP8266. This configuration is to reduce separate micro-controller. The embedded microcontroller and WiFi are made improvements from previous research. This embedded microcontroller is used to send data to the internet through WIFI. This monitoring system can then be accessed using the Cayenne interface. The test results of this tool show that the connection between the microcontroller and the Cayenne application works well through an internet connection. With this tool, users can see real-time data on the use of electrical energy and its cost, as shown in the cayenne dashboard. The voltage sensor test results show an average accuracy is 99.17%. The current sensor testing has an average accuracy rate of 96.9%. On average, the wattage delta between the cayenne dashboard and multimeter measurement is 2.16 watts.